2007
DOI: 10.1128/aac.00410-07
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Activities of Novel Fluoroquinolones Alone and in Combination with Clarithromycin against Clinically Isolated Mycobacterium avium Complex Strains in Japan

Abstract: Our results indicate that the activity of CLR is occasionally attenuated by combination with an FQ both in vitro and in vivo and that this effect seems to be MAC strain dependent. Careful combination chemotherapy using these agents against MAC infectious disease may be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 21 publications
(29 reference statements)
2
40
2
1
Order By: Relevance
“…Thus, our results indicate that it may be difficult to predict the in vivo therapeutic effects of MXF based on its in vitro MIC test result. These results are in agreement with those of a similar study conducted on the Mycobacterium avium complex (32). Factors that could account for this may be differences in the ability of the strain to grow in the medium versus in vivo or differences in the penetrating power of the antibiotics.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Thus, our results indicate that it may be difficult to predict the in vivo therapeutic effects of MXF based on its in vitro MIC test result. These results are in agreement with those of a similar study conducted on the Mycobacterium avium complex (32). Factors that could account for this may be differences in the ability of the strain to grow in the medium versus in vivo or differences in the penetrating power of the antibiotics.…”
Section: Discussionsupporting
confidence: 83%
“…Tomioka et al showed that CLR decreases the activities of gatifloxacin and levofloxacin against M. avium complex strains in vitro (44). Kohno et al also reported that the activity of CLR against M. avium complex strains was attenuated when combined with fluoroquinolones, including MXF, using both in vitro and in vivo models (32). Another study by Bermudez et al revealed that the MXF-AZM combination was significantly less active than AZM alone for the treatment of mice infected with M. avium (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent experimental study revealed that mild antagonism occurred between MXF and CLR when they were given in combination, and this seemed to be MAC strain dependent (26). In addition, using a fluoroquinolones as the only companion drugs for CLR in MAC treatment regimens was associated with the development of CLR-resistant MAC strains (17).…”
Section: Discussionmentioning
confidence: 99%